THE IMPACT OF TURKISH FOREIGN DIRECT INVESTMENTS ON THE ECONOMY OF NORTH MACEDONIA - Derviş, Bülent; Kaprol Muci, Meryem (International Scientific Journal Vision, 2026)
https://doi.org/10.55843/ivisum2611109d With the process of globalization, foreign direct investment (FDI) has come to play a critical role in the economic growth of developing countries. North Macedonia has become an attractive destination for foreign investors due to its strategic location, low tax rates, and investment incentives. The structural characteristics of the country’s economy make it difficult for domestic capital to independently finance large-scale and technology-intensive investments. This situation has made foreign direct investment (FDI) one of the fundamental components of the country’s development strategy. North Macedonia is among the countries in the region with the lowest labor costs per worker. In order to attract foreign investments, the country has reduced employer-paid social security contributions to a minimum level. Through this policy, the financial burden of social security and taxation on both foreign and domestic investors has been reduced, thereby encouraging the inflow of new investments. The incentives implemented to attract foreign investors include exemptions and reductions in personal and corporate income taxes, the elimination of customs duties on raw material imports and other import taxes, as well as labor market regulations designed to facilitate investment activities. Türkiye stands out as one of the major investor countries in North Macedonia. Turkish investments generate not only economic impacts but also significant social effects due to historical and cultural ties between the two countries. In particular, Turkish investments have increased rapidly over the last decade. Turkish firms have investments in various sectors such as banking, insurance, education, healthcare, construction, renewable energy, agriculture and livestock, food production, textiles and apparel, retail trade, and tourism. Recent investments made by Turkish entrepreneurs in North Macedonia have contributed significantly to the development of the country’s industrial sector, employment generation, financial deepening, technology transfer, and regional development.